Finding common(s) ground in the fight for water remunicipalization. (7th December 2018) - McDonald, David A
Abstract: After three decades of privatization, cities around the world are taking water services back under public management and control. The pace of this remunicipalization appears to be growing, with an expanding international movement in favour of publicly-managed water. Does this remunicipalization trend fit with demands for a 'water commons'? Yes and no. Radically different perspectives on what constitutes remunicipalization, combined with an equally diverse set of practices and ideologies on a water commons, denies any easy comparison. Experiences of remunicipalization can run from authoritarian governments reclaiming water for nationalistic control of key resources to radical anti-capitalist politics. So too do notions of water commons cover a broad ideological gamut. The aim of this article is to identify and compare the diverse theoretical underpinnings of water remunicipalization and water commons, seeking points of overlap as well as contradiction. The comparisons reveal multiple points of intersection, and many actually-existing examples of cooperation, but these points of connection also serve to highlight larger ideological chasms in the anti-privatization water movement. In the end, it is less about the labels applied to any particular water policy framework than the philosophical content that shapes its motives and outcomes. In this regard, the terms 'water commons' and 'remunicipalization' serve to obfuscate a varied and sometimes contradictory set of political interventions, necessitating a sharper analytical account of the objectives and actors behind any water initiatives using these names.